2019
DOI: 10.1101/671560
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Chromosome level draft genomes of the fall armyworm, Spodoptera frugiperda (Lepidoptera: Noctuidae), an alien invasive pest in China

Abstract: The fall armyworm (FAW), Spodoptera frugiperda (J.E. Smith) is a severely destructive pest native to the Americas, but has now become an alien invasive pest in China, and causes significant economic loss. Therefore, in order to make effective management strategies, it is highly essential to understand genomic architecture and its genetic background. In this study, we assembled two chromosome scale genomes of the fall armyworm, representing one male and one female individual procured from Yunnan province of Chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
58
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(62 citation statements)
references
References 62 publications
3
58
1
Order By: Relevance
“…Our new assembly has a higher proportion of complete BUSCO genes than the assembly by Liu et al ( Table 1). In addition, our new assembly has a lower proportion of duplicated BUSCO genes (28/1658 = 1.69%) than the assemblies from Liu et al 25 (134/1658 = 8.08% for male assembly, 97/1658 = 5.86% for female assembly). From this BUSCO analysis, we concluded that our assembly has higher accuracy than the assemblies from Liu et al 25 .…”
Section: Reference Genome and Resequencing Datamentioning
confidence: 60%
See 3 more Smart Citations
“…Our new assembly has a higher proportion of complete BUSCO genes than the assembly by Liu et al ( Table 1). In addition, our new assembly has a lower proportion of duplicated BUSCO genes (28/1658 = 1.69%) than the assemblies from Liu et al 25 (134/1658 = 8.08% for male assembly, 97/1658 = 5.86% for female assembly). From this BUSCO analysis, we concluded that our assembly has higher accuracy than the assemblies from Liu et al 25 .…”
Section: Reference Genome and Resequencing Datamentioning
confidence: 60%
“…In addition, our assembly has better contiguity because of a much smaller number of contigs and a much smaller L90 value than the assembly by Liu et al 25 (Table 1).…”
Section: Reference Genome and Resequencing Datamentioning
confidence: 79%
See 2 more Smart Citations
“…Smith) (Lepidoptera: Noctuidae), an invasive pest native to tropical and subtropical America, is an economically destructive pest (Midega et al ). FAW has been dispersed from its native region invading Africa in 2016 (Goergen et al ) and many Asian countries in 2018 (Liu et al ). FAW attacks maize and other graminaceous crops, and its host range includes 186 plant species in 42 families (Casmuz et al ).…”
Section: Introductionmentioning
confidence: 99%